Bioadsorbents from algae residues for heavy metal ions adsorption: chemical modification, adsorption behaviour and mechanism. Issue 20 (6th September 2021) - Li, Rongguo; Zhang, Tingting; Zhong, Haifeng; Song, Weikang; Zhou, You; Yin, Xueqiong
ABSTRACT: Biosorption is an emerging technology for the removal of heavy metals from industrial wastewater by natural or modified biomass. In this study, we proposed a novel protocol for making full use of seaweeds. Brown seaweed Sargassum carpophyllum residue (SCR) and green seaweed Caulerpa lentillifera residue (CLR) were obtained after extraction of the bioactive polysaccharides. The obtained residues were further chemical modified by butanedioic anhydride to obtained respective carboxylated product, named CSCR and CCLR. According to the titration results, CSCR and CCLR contained 2.77 and 2.12 mmol/g of carboxyl group. After modification, the adsorption capacity for metal ions increased by 3–6 times. The adsorption capacity of CSCR for Cu 2+, Pb 2+, Cd 2+ and Mn 2+ was 52.37, 107.11, 85.62, and 43.52 mg/g, and that of CCLR was 78.10, 108.80, 87.30 and 57.80 mg/g, respectively. The adsorption was well described by the pseudo-second-order kinetic model and Langmuir adsorption isotherm equation. GRAPHICAL ABSTRACT: UF0001